Implications of Infertility in Building Household Integrity From an Islamic Legal Perspective (Study in Parepare City) - Silvana Herman; Rusdaya Basri; Zainal Said; Sudirman L; Hannani (Universitas Muhammadiyah Palu, 2024)
The main study in this research is the Implications of Infertility in Fostering Household Integrity from an Islamic Legal Perspective (Study in Parepare City). In fact, the purpose of marriage is not only to worship, but also to produce offspring. The results of the research show that (1) There is a mismatch in the expectations of married couples in having children in the city of Parepare, which is not the least of married couples in the city of Parepare who experience infertility. (2) Factors that influence the household integrity of couples who experience infertility in the city of Parepare are Religion, Love and Economics (3) The implication of infertility for couples who experience it in the city of Parepare is that there is a lot of pressure from the family to immediately give birth to children. Which ultimately gives rise to a deep sense of disappointment felt by the sufferer. So some sufferers choose to practice polygamy and adopt children from their own families.